There's always the river: social and environmental equity in rapidly urbanising landscapes in India. (3rd April 2018) - Dempsey, Nicola; Jayaraj, Smriti Rabina; Redmond, Emily
Abstract: In the pursuit of sustainable and liveable cities, Indian built environment practitioners and policy-makers are understandably focused on aspects of infrastructure, sanitation and health, given the significant urban problems of pollution and environmental degradation. However, there is limited empirical examination of Indian towns and cities as changing urban landscapes. To explore this, the paper examines the rivers in two rapidly urbanising Indian cities. It calls on interviews with practitioners, residents and users in Madurai and Ahmedabad, focusing on access and use of the river to explore social and environmental equity. The findings suggest that free, public and safe access to the rivers have reduced over time in both cities, for different reasons. Perceived environmental quality of both rivers has also worsened and the associated cultural meanings, held by riparian users, have changed. We suggest that urban river infrastructure should be reconceptualised to explore the feasibility and acceptability of a more holistic approach to understanding Indian riparian urban landscapes.